Pemanfaatan Teknologi dalam Perkembangan Operasional Perbankan Syariah - Bayu Aji Laksono; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
In the current digital era, the utilization of technology is becoming increasingly important for the banking industry, including Islamic banking. Several reasons why technology must be a major focus for the development of Islamic banking are to improve operational efficiency, expand service reach, enhance customer experience, drive product innovation, and strengthen security and compliance. This study discusses the utilization of technology in the operational development of Islamic banking in Indonesia, as well as the challenges and opportunities faced by the industry in adopting digital technology. Thus, this study provides valuable insights into the dynamics of the development of Islamic banking in Indonesia, particularly in the context of utilizing digital technology to improve the industry's operations and competitiveness.